2021
DOI: 10.1093/schizbullopen/sgab005
|View full text |Cite
|
Sign up to set email alerts
|

Pitch and Duration Mismatch Negativity are Associated With Distinct Auditory Cortex and Inferior Frontal Cortex Volumes in the First-Episode Schizophrenia Spectrum

Abstract: Background Pitch and duration mismatch negativity (pMMN/dMMN) are related to left Heschl’s gyrus gray matter volumes in first-episode schizophrenia (FESz). Previous methods were unable to delineate functional subregions within and outside Heschl’s gyrus. The Human Connectome Project multimodal parcellation (HCP-MMP) atlas overcomes this limitation by parcellating these functional subregions. Further, MMN has generators in inferior frontal cortex, and therefore, may be associated with inferior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 72 publications
2
13
1
Order By: Relevance
“…Based on several lines of study [52,53], duration MMN holds promise as a biomarker for schizophrenia as this deviant type is shown to be reduced in those with EPP, more so than other deviant types. However, our results, along with other studies [54][55][56], are not homogeneous to this, which speaks to the ambiguity and instability of MMN as a biomarker for schizophrenia. Specifically, it has been demonstrated that effect size of observed MMN reductions are smaller in EPP compared to the chronic illness [52]; this is somewhat mirrored by the small effect sizes between groups observed in the present study.…”
Section: Discussion/conclusioncontrasting
confidence: 99%
“…Based on several lines of study [52,53], duration MMN holds promise as a biomarker for schizophrenia as this deviant type is shown to be reduced in those with EPP, more so than other deviant types. However, our results, along with other studies [54][55][56], are not homogeneous to this, which speaks to the ambiguity and instability of MMN as a biomarker for schizophrenia. Specifically, it has been demonstrated that effect size of observed MMN reductions are smaller in EPP compared to the chronic illness [52]; this is somewhat mirrored by the small effect sizes between groups observed in the present study.…”
Section: Discussion/conclusioncontrasting
confidence: 99%
“…Further, FEP were deficient in enhancing cortical activity with attention across these regions as well, suggesting that they have relatively widespread sensory and attention modulation deficits in auditory cortex, encompassing primary and nonprimary auditory cortex. The specificity of localizing this functional deficit in primary and auditory belt regions may provide insight to the emergence of psychosis, as specific temporal lobe abnormalities (e.g., Heschl's gyrus gray matter reduction) are present very early in the disorder (Curtis et al, 2021 ; Kasai et al, 2003 ) and show progressive pathology with disease duration (Salisbury et al, 2007 ). Understanding how the underlying progressive pathology relates to decline in functional abilities such as auditory attention modulation can provide a better understanding of this interplay at the emergence of psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…We characterised how LFP and ECoG spectra are modulated during ketamine exposure with and without pre-administration of naltrexone or clozapine. We recorded drug-induced LFP/ECoG in freely moving rats from four brain structures relevant to schizophrenia and major depressive disorder: LFPs from the thalamus ( 54 60 ), prefrontal cortex (PFC) ( 61 64 ), the nucleus accumbens (NAc) ( 65 69 ), and ECoG above the auditory cortex (AC) ( 70 76 ). To control for behavioural states, data from head-mounted accelerometers were utilised to algorithmically define if the animal was active or passive in each LFP/ECoG window.…”
Section: Introductionmentioning
confidence: 99%